2019
DOI: 10.1016/j.psychres.2018.12.115
|View full text |Cite
|
Sign up to set email alerts
|

Factors prospectively associated with physical activity and dietary related outcomes in people with severe mental illness: A systematic review of longitudinal studies

Abstract: Understanding factors that contribute towards physical activity and diet outcomes are important for health improvement in people with severe mental illness. Cross-sectional findings on factors associated with diet and physical activity outcomes provide limited information on what predicts changes or longterm outcomes in lifestyle behaviours in people with severe mental illness. A systematic review was therefore conducted to identify prospective studies with quantitative data on baseline factors associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Higher patients’ aerobic fitness levels are linked to lower FC between parts of the subcortical nuclei (basal ganglia, thalamus and amygdala [ 50 ]) and the cerebellum leading to attenuated total symptom severity. This is in line with previous studies suggesting a beneficial relation between aerobic fitness and different domains of psychiatric symptoms [ 22 , 71 , 72 ]. Within this association, our results are the first underlining the mediating role of FC between the subcortical nuclei and the cerebellum.…”
Section: Discussionsupporting
confidence: 93%
“…Higher patients’ aerobic fitness levels are linked to lower FC between parts of the subcortical nuclei (basal ganglia, thalamus and amygdala [ 50 ]) and the cerebellum leading to attenuated total symptom severity. This is in line with previous studies suggesting a beneficial relation between aerobic fitness and different domains of psychiatric symptoms [ 22 , 71 , 72 ]. Within this association, our results are the first underlining the mediating role of FC between the subcortical nuclei and the cerebellum.…”
Section: Discussionsupporting
confidence: 93%
“…Numerous studies showed a higher prevalence of smoking among schizophrenia patients [ 9 , 10 , 11 , 12 , 13 ]. In Jakobsen et al’s [ 13 ] study, more than half of the participants (52.1%) reported daily smoking, whereas in Heald et al [ 11 ], 64.9% were smoking.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to an elevated body mass index (BMI), studies of body composition have shown an increased proportion of fat tissue and a decreased proportion of muscle mass [ 7 , 9 ]. Several factors that may contribute to this are indicated in the literature: socioeconomic factors [ 10 ], use of tobacco products [ 11 , 12 ], poorer dietary habits [ 13 ], low physical activity [ 14 ], and metabolic disorders caused by antipsychotic therapy [ 7 , 15 ]. The poorer dietary habits are manifested through a high intake of fat, saturated fatty acids, sugar, and alcohol on one side and a reduced intake of fiber, fruits, vegetables, and fish on the other [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%